2019
DOI: 10.15666/aeer/1701_969982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar on Cadmium, Nickel and Lead Uptake and Translocation in Maize Irrigated With Heavy Metal Contaminated Water

Abstract: This study was conducted to investigate the effect of biochar on bioavailability reduction of cadmium (Cd +2 ), nickel (Ni +2 ), and lead (Pb +2 ) and its subsequent effects on soil properties and maize plant growth in a soil which was irrigated by contaminated water with above heavy metals. Twelve different biochar were prepared under two temperatures of 500 °C and 700 °C by using six biomass including residuals of wheat (WB), chickpea (CB), maize (MB), reed (RB), olive (OB) and sugarbeet (SB). Physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The metals (Pb and (Cd) hampered seed germination toxicity even at low levels; similar results were found in seed germination characteristics studies [25]. Such suppression of seed germination could be due to the interference of metals with the essential enzymes for seed germination (amylase and protease).…”
Section: Seed Germinationsupporting
confidence: 73%
“…The metals (Pb and (Cd) hampered seed germination toxicity even at low levels; similar results were found in seed germination characteristics studies [25]. Such suppression of seed germination could be due to the interference of metals with the essential enzymes for seed germination (amylase and protease).…”
Section: Seed Germinationsupporting
confidence: 73%
“…Similarly, Sayyadıan et al [101] reported that biochar application from different origins decreased the extractable Ni, Pb, and Cd contents of the soil and consequently decreased the Ni, Pb, and Cd contents of both root and root parts of maize [102]. They also reported that biochar application to the environment contaminated with Pb, Cd, and Cr caused a decrease in the Cd, Pb, and Cr contents of both the soil and the corn plant.…”
Section: Discussionmentioning
confidence: 92%
“…Cation exchange is another important mechanism that plays a role when removing Pb(II) from water using biochar [18,93]. Biochar properties consist of cations such as Na, K, Ca, Mg, etc.…”
Section: Ion Exchangementioning
confidence: 99%